Revoicing the Maulid Across Worlds: Intertextual and Transtextual Reconfiguration of Syaraf al-Anām in the Gorontalonese Kitabi lo Dikili - Muhammad Fadhlurrahman Zakaria; R. Yani'ah Wardani; Fouad Larhzizer (Center for Research and Development of Religious Literature and Heritage, 2025)
This study examines the textual relationship between the Arabic Maulid manuscript Syaraf al-Anām and its Gorontalonese Kitabi lo Dikili, a relationship that has not been systematically analyzed in previous research. Existing studies tend to focus either on Arabic Maulid texts or on local ritual manuscripts, leaving a gap in understanding how a canonical Arabic composition is reshaped through vernacular, performative, and paratextual adaptation within Indonesian ritual contexts. The study employed a qualitative comparative approach using two primary manuscripts and direct observation of the Modikili ceremony in Gorontalo. Data include Arabic and Pegon-script texts, which are analyzed through close reading and coded using Kristeva’s intertextuality and Genette’s transtextuality to identify structural, linguistic, and paratextual correspondences. The findings show three major patterns. First, Kitabi lo Dikili revoices its Arabic source through vernacular translation, condensed phrasing, and culturally embedded metaphors. Second, the manuscript introduces 62 jabu refrains and distinctive Pegon orthographic features that function as paratextual cues for oral performance. Third, ritual observation demonstrates that communal recitation sustains the authority and continuity of the text as living heritage. These results highlight how Islamic devotional literature circulates across linguistic and ritual environments through creative adaptation. The study concludes that examining Arabic and vernacular Maulid manuscripts together provides a more integrated understanding of textual continuity, localization, and the dynamics of Islamic literary heritage in Indonesia.